2008
DOI: 10.1021/ic801193r
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Valence Creutz−Taube Ion Analogues Incorporating Thiacrowns: Synthesis, Structure, Physical Properties, and Computational Studies

Abstract: A series of nine new complexes incorporating [Ru(II)Cl([n]aneS(3))] (n = 12, 14, 16) metal centers bridged by three ditopic ligands containing two monodentate sites (pyrazine, 4,4'-bipyridine, and 3,6-bis(4-pyridyl)-1,2,4,5-tetrazine) have been synthesized and fully characterized. The solid-state structures of three of the complexes have been further characterized by X-ray crystallography studies. Intermetallic interactions within the new systems have been probed using electrochemistry and optical spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
3
14
0
Order By: Relevance
“…A similar trend for ligand-centered couples is observed when complex 4 + is compared to 5 + and 6 + : the relevant oxidation couples for the [12]aneS 4 complex are between 50 and 120 mV less positive than comparable oxidations for the other two complexes. These data are consistent with previous experimental and DFT studies showing that, because of its smaller coordination cavity, back-bonding interactions are weaker in [12]aneS 4 than in the larger thiacrowns, , which results in less stabilization of the Ru d(π) orbitals and hence less positive Ru III/II couples.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A similar trend for ligand-centered couples is observed when complex 4 + is compared to 5 + and 6 + : the relevant oxidation couples for the [12]aneS 4 complex are between 50 and 120 mV less positive than comparable oxidations for the other two complexes. These data are consistent with previous experimental and DFT studies showing that, because of its smaller coordination cavity, back-bonding interactions are weaker in [12]aneS 4 than in the larger thiacrowns, , which results in less stabilization of the Ru d(π) orbitals and hence less positive Ru III/II couples.…”
Section: Resultssupporting
confidence: 92%
“…Related to this topic, the Thomas and Félix groups have investigated the effect of a series of thiacrown ligands on the redox properties of ruthenium(II) centers , and used these fragments in the construction of mixed valence, MV, complexes. Generally, it was found that, because of back bonding interactions involving overlap of C–S σ* orbitals that are in-plane with occupied t 2g metal orbitals, the thiacrowns stabilize the Ru II state more than even polypyridyl ligands, and this effect increases as the number of S donors within the thiacrown increases. However, comparisons of MV systems containing macrocycles with the same number of S donors, revealed that changes in the size of the macrocycle also tune the intermetallic interaction and the overall redox chemistry of the entire system, presumably by changing the extent of the C–S σ*/t 2g overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine-based nitrogen-donor ligands, such as 4,4′-bipyridine (4,4′-bpy) fall within this category, and can additionally be used in the synthesis of bridged multinuclear metal complexes 11 , 14 16 . The ability of 4,4′-bpy to form bimetallic complexes coupled with its known impact on the redox nature of coordinated metals leads to questions about electronic communication between the metal centers, as well as unusual magnetic properties 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there have been many studies on conjugated organometallic molecular wires in recent years. The electronic interaction between the two redox-active metal centers mainly depends on the conjugated organic bridge ligand . Previous research in this area has mainly focused on linear conjugated metal complexes with sp- and sp 2 -hybridized organic bridges, such as oligoethynyl- and oligovinyl-bridged metal complexes.…”
Section: Introductionmentioning
confidence: 99%